2023
DOI: 10.1152/ajplung.00119.2022
|View full text |Cite
|
Sign up to set email alerts
|

α1 Adrenoreceptor antagonism mitigates extracellular mitochondrial DNA accumulation in lung fibrosis models and in patients with idiopathic pulmonary fibrosis

Abstract: Idiopathic Pulmonary Fibrosis is increasingly associated with nerve-driven processes and endogenous innate immune ligands such as mitochondrial DNA (mtDNA). Interestingly, a connection between these entities has not been explored. Here we report that noradrenaline (NA) derived from the lung's adrenergic nerve supply drives αSMA-expressing fibroblast accumulation via mechanisms involving α1 adrenoreceptors and mtDNA. Using the bleomycin model, we compared ablation of the lung's adrenergic nerve supply to surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 67 publications
2
11
1
Order By: Relevance
“…Our data indicate that the administration of terazosin in nebulized form did not impact lung inflammation, airway compliance or resistance, collagen accumulation, or histologic measures of lung remodeling in the bleomycin and TGFβ1-Tg + models of murine pulmonary fibrosis. These results are in contrast to prior work in which intraperitoneal administration of terazosin modulates fibrotic changes in bleomycin challenged mice [17] and numerous studies demonstrating that ⍺ 1 -AR blockade improves fibrotic endpoints in cross-organ models of tissue fibrosis including the lung, liver, heart, and kidney [41][42][43][44]. Notably, because the present study assessed localized tissue delivery as opposed to systemic ⍺ 1 -AR antagonism, our data indicate that alternate approaches will be required to support the repositioning of this drug for the treatment of lung fibrosis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our data indicate that the administration of terazosin in nebulized form did not impact lung inflammation, airway compliance or resistance, collagen accumulation, or histologic measures of lung remodeling in the bleomycin and TGFβ1-Tg + models of murine pulmonary fibrosis. These results are in contrast to prior work in which intraperitoneal administration of terazosin modulates fibrotic changes in bleomycin challenged mice [17] and numerous studies demonstrating that ⍺ 1 -AR blockade improves fibrotic endpoints in cross-organ models of tissue fibrosis including the lung, liver, heart, and kidney [41][42][43][44]. Notably, because the present study assessed localized tissue delivery as opposed to systemic ⍺ 1 -AR antagonism, our data indicate that alternate approaches will be required to support the repositioning of this drug for the treatment of lung fibrosis.…”
Section: Discussioncontrasting
confidence: 99%
“…Adrenergic hyperinnervation and the accumulation of ⍺ 1 -adrenoreceptor (⍺ 1 -AR) expressing cells are associated with fibrosis in animal models, where interruption of adrenergic signaling via chemical denervation and ⍺ 1 -AR antagonism mitigates fibrotic endpoints [17,19]. It has further been shown that in some settings the blood [20] and lungs [19] of IPF patients are enriched for noradrenaline, and that IPF patients prescribed ⍺ 1 -AR antagonists for non-pulmonary indications experience improved survival [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rassler et al (8) reported that during NE stimulation, α-adrenergic mechanisms mainly contribute to pulmonary remodeling. A recent study showed that the α 1 -AR antagonist terazosin mitigates lung fibrosis caused by NE elevation due to bleomycin stimulation (27). However, the premise of this conclusion is that bleomycin leads to significantly increased expression of three α 1 -AR subtypes, especially α 1D -AR, in pulmonary tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The adrenal glands are important regulators of systemic homeostasis and respond to various stimuli via their production of catecholamines and aldosterone (ALD). Emerging studies suggest that fibrosis is associated with catecholamines such as adrenaline (AD) and noradrenaline (NA) [6][7][8][9][10]. Additionally, work from our lab has shown that NA derived from lungspecific adrenergic nerves contributes to pulmonary fibrosis [6,8,11] which was ameliorated with alpha-adrenergic receptor 1D (ADRA1D) antagonism [8].…”
Section: Introductionmentioning
confidence: 99%